Match analysis in a wheelchair tennis tournament - Sanchez-Pay, A.; Sanz-Rivas, D.; Torres-Luque, G. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to analyze the activity patterns of wheelchair tennis matches. 16 male singles tennis matches were played. Eight internationally ranked players were recorded and subsequently analyzed according to the following variables: total playing time, effective playing time, resting time (both in absolute values and as a percentage of total time). The average rally duration and the number of shots per rally were also recorded. The results showed a mean (SD) of match length of 61.70 (14.33) minutes, a effective playing time of 20.07 (3.67) %, a work:rest time ratio of 1:4.12 and an average duration of point of 6.93 (5.16) seconds. Most of the points end in 3 or less shots. No significant differences were found in rally duration and shots per rally with regards to non-breakpoint opportunities and breakpoint opportunities (p>0.05). Knowledge of the activity patterns within competition helps with specific training for the sport.